AI-Powered Social Media Marketing and Digital Wallet Adoption for SMEs in Tanjung Morawa District - Esther Praja Anggriany Panggabean; Mas Intan Purba; Isna Asdiani Nasution; Rafida Khairani; Tantri Octora Dwi Syah Putri; Jholant Bringg Luck Amelia Br Sinaga; Nurul Wardani Lubis (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Digital transformation has opened opportunities for Small and Medium Enterprises (SMEs) through innovative technology utilization. However, many SME operators in Tanjung Morawa District, Deli Serdang Regency, have limited understanding of social media marketing strategies and digital wallet benefits. This community service activity aims to enhance SME operators' knowledge in utilizing AI-supported social media marketing and digital wallet usage to improve business competitiveness. The method is participatory approach with socialization, training, and practice mentoring conducted at Tanjung Morawa District Head Office on May 26, 2025, targeting 15-20 SME operators. Activity stages included preparation, implementation (social media marketing socialization, AI training for business storytelling, and digital wallet benefits socialization), and closing. Results showed significant changes in participants' understanding. Pre-training surveys revealed 78% of participants never used AI for business purposes, and 65% relied on conventional marketing methods. After training, there was 45% increase in post-test scores, 85% successfully created business storytelling content using AI, and 90% expressed interest in using digital wallets. This activity successfully transformed SME operators' understanding of digital marketing from limited to comprehensive and practical, enabling active participation in competitive digital economy.